Strategic principles in the system of organization of health education in schools and universities - Афонін, А. П. (Pedagogy of Higher and Secondary Education, 2012)
Afonin A. P. Strategic principles in the system of organization of health education in schools and universities. The priority task of pedagogical stall that capable of working creatively and efficiently in new conditions with the use of health preservation principles of education and upbringing of rising generation are analyzed.